Imaging of a patterned and buried molecular layer by coherent acoustic phonon spectroscopy - Hettich, Mike (2012)
A molecular layer of aminopropyltriethoxysilane is patterned with a focused ion beam and subsequently covered by a gold film. The gold-polymer-substrate structures are afterwards imaged by ultrafast coherent acoustic phonon spectroscopy in reflection geometry. We demonstrate that the lateral structure of the covered polymer layer can be detected via the damping time of the vibrational mode of the gold film. Furthermore, we utilize Brillouin oscillations originating from the silicon substrate to map the structures and to estimate the molecular layer thickness.